DEVELOPMENT OF FORMING MECHANISMS OF EFFECTIVE HUMAN RESOURCES DEVELOPMENT POLICY IN THE REGIONAL ECONOMY (ON THE EXAMPLE OF THE PAVLODAR REGION) - А. A. Titkov,; S.Zh. Ibraimova,; E.K. Aibuldinov,; M.K. Karimbergenova, (Academic Journal of Physical and Chemical Sciences, 2019)
The article considers the current economic situation in the field of human resources development of the leading industrial region of the Republic of Kazakhstan – Pavlodar region. Special attention is focused on quantitative and qualitative indicative indicators of the state of human resources in the dynamics.In the course of the research, on the basis of statistical and analytical analysis, the main conceptual problems of the development of the human resources potential of the region, including labor potential and human capital, are identified.The detailed systematization of the problems of human resources development in the region by quantitative and qualitative components has also been made. The following were identified as the leading priorities in the formation of mechanisms for an effective human resources development policy: implementation of measures to enhance the role of industrial production in the development of human resources, through the instruments of social responsibility, allocation of grants for training and retraining of personnel; establishment of a regional corporate university; intensification of investment in increasing the level of demographic attraction of the region.